2018
DOI: 10.3389/fchem.2018.00542
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interaction Between Interfacial Structure and Fibrinogen at Blood-Compatible Polymer/Water Interface

Abstract: The correlation between the interfacial structure and protein adsorption at a polymer/water interface was investigated. Poly(2-methoxyethyl acrylate)(PMEA), which is one of the best blood compatible polymers available, was employed. Nanometer-scale structures generated through the phase separation of polymer and water were observed at the PMEA/phosphate buffered saline interface. The interaction between the interfacial structures and fibrinogen (FNG) was measured using atomic force microscopy. Attraction was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…Research supporting this result was reported recently from the interaction force measurement between fibrinogen and PMEA, 89 and the molecular weight dependence of PMEA on the interfacial structure and the blood compatibility. 90 We speculate that the water-rich region prevents the adsorption of fibrinogen, because much intermediate water exists there.…”
Section: Observation Of Pmea/air and Pmea/water Interfacessupporting
confidence: 85%
“…Research supporting this result was reported recently from the interaction force measurement between fibrinogen and PMEA, 89 and the molecular weight dependence of PMEA on the interfacial structure and the blood compatibility. 90 We speculate that the water-rich region prevents the adsorption of fibrinogen, because much intermediate water exists there.…”
Section: Observation Of Pmea/air and Pmea/water Interfacessupporting
confidence: 85%
“…Polymers often exhibit their functions in water, or in the presence of water, that is not just a solvent but plays an important role in the expression of functions. The water molecules related to those functions exist in the vicinity of the polymers and, compared to bulk water, have different properties, which have been studied by various techniques such as differential scanning calorimetry (DSC), 1 , 2 neutron reflectometry, 3 5 atomic force microscopy, 6 and contact angle measurements. 7 , 8 Vibrational spectroscopy has been used to analyze the structural and dynamical properties of aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…To understand how IW contributes to the blood compatibility of the hydrated polymers, several studies have investigated the interfacial structure of PMEA analogues at the polymer/water interface. Regular nanometer-scale protrusions were found at the PMEA analogue/water interfaces, while irregular large aggregates were observed at the interface between nonblood compatible polymers such as poly­( n -butyl acrylate) (PBA) and water. The protruded interfacial structure was suggested to be a phase separation of the polymer and water in the interface region resulting from the partial entanglement of polymers with the bulk polymer phase. , The protrusions (called polymer-rich regions) of both blood- and nonblood-compatible polymers adsorbed more fibrinogen than the flat regions (called water-rich regions) . In addition, the fibrinogens, which were adsorbed on the surface of blood-compatible polymers, exhibited less denaturation behavior and easily desorbed from the surface in comparison with those on the surface of nonblood-compatible polymers. , Therefore, water molecules in the water-rich regions have been suggested to have a capacity for preventing fibrinogen adsorption and denaturation, and IW molecules would play an important role in this preferred characteristic. , …”
Section: Introductionmentioning
confidence: 99%